31. EVALUATION OF MARKETING ACTIVITIES FOR MEDICAL EXAMINATION ON DEMAND AT VIETDUC UNIVERSITY HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objectives: The study aims to evaluation of marketing activities for medical examination on demand at Viet Duc University Hospital in 2023; describe and analyze some factors related to this activity at the hospital.Method: Cross-sectional descriptive research. The survey subjects including 200 patients with outpatient medical examinations and the hospital's leadership and medical staff through the available toolkit. Evaluation of marketing activities for medical examination and treatment on demand classified into 5 aspects including marketing: information system, marketing strategy, marketing mix, marketing execution plan and marketing assessment.Results: Evaluation of marketing activities performed at a good level (80/100 points). Marketing Strategy and Marketing Evaluation activities were implemented most fully, achieving the highest score (converted score of 0.9 points). The internal factors given are human factors, internal operational policy factors and hospital facilities factors.Conclusion: Marketing activities of medical examination services of Viet Duc University Hospital in 2023 reached a good level. However, it is necessary to promote strengths in mixed marketing activities, improve operating budget factors, service delivery channels and service prices and promote internal policies.
Keywords: Hospital marketing; examination on demand; Viet Duc University Hospital